Wealth Effects on Consumption in Switzerland - Frank Schmid (Swiss Journal of Economics and Statistics, 2013)
This paper studies the role of wealth fluctuations for aggregate consumption in Switzerland. In the long-run, wealth is found to have a significant effect on consumption. In the short-run, by contrast, the effects are less clear as consumption and wealth sometimes deviate persistently from equilibrium. Such deviations from equilibrium can have a duration of up to 3 years. If these equilibrium deviations are due to rapid wealth growth, Swiss consumers expand their consumption spending less than they could because they perceive large parts of these wealth gains as merely transitory. While they do not adapt to transitory wealth changes, they eventually react to the permanent wealth changes. On average, 80% of the variation in Swiss wealth that lasts for at least 24 quarters is permanent and it is exactly to those permanent lasting shocks that Swiss consumers react. Because consumption and wealth both react to the same permanent shocks, these results can be interpreted as evidence that consumers react less to changes in wealth per se than to changes in the business cycle.
Keywords: E21; C32; 330; VECM model; wealth effects; private consumption; Switzerland